Simulation of Liquid Metal Droplets from Field Emission (Communications in Computational Physics, 2007)
Liquid metal droplets are accelerated by electrostatic forces in a processknown as field emission. In this study, we simulate the emission of charged indiumdroplets on a needle in 2D cylindrical coordinates. The boundary element method isused to rapidly and accurately calculate the electric field on the fluid surface, whichis then advected forward in time using level sets. This is the first time these methods have been combined, and this combination addresses difficult detachable surfacetracking issues successfully. A histogram of droplet charge-to-mass ratio is generatedin which it is predicted that smaller satellite droplets are more densely charged. Inaddition, our model is compared with independent pre- and post-snap off data andproduces good agreement with the result.